Dampak Pengangguran dan Penyaluran Dana Zakat Infak Sedekah terhadap Kemiskinan di Provinsi Kalimantan Selatan - Muhammad Ramadhani; Difi Dahliana (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2022)
This study aims to determine the effect of unemployment and ZIS funds' distribution on South Kalimantan poverty. This is a quantitative study with secondary data in the form of time series data for 2012-2021 obtained from the Central Statistics Agency (BPS) and the National Amil Zakat Agency (BAZNAS). Based on the results of statistical analysis using the Eviews 9 application, it is assumed that all the requirements in the classical assumptions are met so that multiple linear regression analysis can be carried out with t-test and f-test. The results of this study indicate that the unemployment rate and the distribution of ZIS funds simultaneously have a significant effect on the poverty level in South Kalimantan. However, partially, only the unemployment rate has a considerable effect. In contrast, the distribution of ZIS funds does not have a substantial impact because consumptive, not productive; programs still dominate the distribution pattern of ZIS funds. Therefore, this study resulted in a recommendation to increase the distribution of ZIS funds productively to impact poverty alleviation in South Kalimantan significantly.